1982
DOI: 10.2118/9815-pa
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for Structuring Surfactants To Maximize Solubilization of Oil and Water: Part 1—Commercial Nonionics

Abstract: The phase behavior of nonionic surfactants having the same hydrophilic/lipophilic balance (HLB) but differing molecular weights has been studied. It is shown that the optimal alkane carbon number (ACN) depends on the HLB, but that increasing the hydrophobe molecular weight narrows the middle phase region, increases the solubilization parameter, and decreases the interfacial tension (IFT). We found that the width of the three-phase region is in simple inverse proportion to the solubilization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…For instance, in Figure 10, an intermediate degree of branching (isomer 5φ) results in the lowest value of the minimum in interfacial tension (67), noted as (γ min ) min . It has also been reported that in a lnS -ACN compensated variation, the width of the three-phase region, either as ∆S or ∆ACN, is inversely related to the value of solubilization (63). On the other hand, other compensating changes-for instance, (i) an increase in oil ACN and surfactant alkyl chain length (68,69) or (ii) an increase in EON and an increase in salinity (59)-seem not to affect the solubilization in a significant way.…”
Section: Solubilization Enhancement With a Single Amphiphilic Speciesmentioning
confidence: 91%
“…For instance, in Figure 10, an intermediate degree of branching (isomer 5φ) results in the lowest value of the minimum in interfacial tension (67), noted as (γ min ) min . It has also been reported that in a lnS -ACN compensated variation, the width of the three-phase region, either as ∆S or ∆ACN, is inversely related to the value of solubilization (63). On the other hand, other compensating changes-for instance, (i) an increase in oil ACN and surfactant alkyl chain length (68,69) or (ii) an increase in EON and an increase in salinity (59)-seem not to affect the solubilization in a significant way.…”
Section: Solubilization Enhancement With a Single Amphiphilic Speciesmentioning
confidence: 91%
“…Although fluid components do fractionate in the middle-phase environment, dynamic contacting studies indicated that large differ-808 ences between oil/microemulsion-phase mobilities would be required to affect optimum conditions severely. 10. As with clays, sodium and ammonium ions have very different affinity constants for the CROS that affect phase behavior; calcium and magnesium ions have nearly the same affinity for the CROS.…”
Section: Discussionmentioning
confidence: 99%
“…The mole fraction weighted of hydrocarbon EACN (Eq. 3) as proposed by Cayias et al [25] and Cash et al [26] has been widely used to estimate the EACN mix of heavy hydrocarbon mixtures, at atmospheric pressure [6,15,[27][28][29].…”
Section: Theoretical Sectionmentioning
confidence: 99%